Rancang Bangun Aplikasi Majalah STIKOM Surabaya News Berbasis Mobile - Rahmattullah, Moch. Farizal; Wurijanto, Tutut; Sutanto, Teguh (Jurnal JSIKA, 2012)
STIKOM Surabaya News or commonly called SSNews is a campus magazine of STIKOM Surabaya that containing a variety of news and information about both the activities around campus and variety of general information. SSNews printed version is have to form as a magazine that can be obtained on campus, but the number of copies printed is relatively limited to meet the needs of readers, specially those on either campus environment for students, faculty or staff. Therefore SSNews have another alternative to launch an online version that can be accessed through the site http://ssnews.stikom.edu/ which can be accessed easily via the computer. Currently readers can only access the address of the website through the browser on mobile phones so as to make the readers should be online to enjoy every news content on SSNews, moreover not all of it can display websites very well and comfortable. Since the majority of readers are mobile phone users, the authors offer a new alternative for the reader by making an application that called SSNews Mobile which provides a new experience in reading the news content of SSNews. By using SSNews Mobile, readers can enjoy SSNews contents with relatively cheaper and more comfortable. Even the news that you want to save is can be done so quickly and easily so that the readers does not need to online anymore to read news content.   Keywords : SSNews, Magazine, Mobile Application, J2ME.